Some Economic and Demographic Consequences of Mental Illness - Bartel, Ann; Taubman, Paul (Journal of Labor Economics, 1986)
This article uses a unique data set to measure the economic and demographic consequences of mental illness. We find that mental illness significantly reduces an individual's earnings and that in some cases this effect lasts as long as 15 years. Mental illness is also shown to affect an individual's ability to marry or stay married, lowers the number of children that he has, and encourages his wife to work.